Educação vigiada: como o capitalismo de vigilância opera na plataforma Google Workspace for Education Fundamentals - Ferraro, Danielle Soares e Silva Bicudo (2022)
The research has as a goal to understand how the surveillance capitalism operates on Google’s remote learning platform, Google Workspace for Education Fundamentals. The surveillance capitalism is a mutation of the informational capitalism, and it is related to the use of remote communication and information technologies. Nowadays, it is the business model of large technology companies, the Big Techs, and it is based on the continuous capture of data generated through day-by-day actions mediated by digital communication devices, in exchange for supposedly free services. In this way, these captured data generate behavioral surplus, the main product of a market that seeks to establish patterns about our tastes, behaviors, displacements, and consumption habits – and, if possible, to predict and control them. From this perspective, the coronavirus pandemic, in addition to exposing the infrastructure and technology problems resulting from the commodification of education in the country and from cuts in the investment in the area of education, accelerated the “digitization” of this market. For months, classrooms have been transported to remote teaching platforms, in virtual learning environments. Thus, if on the one hand, digital tools made it possible to continue teaching activities, on the other hand, they ended up putting children and adolescents in direct contact with surveillance capitalists, in particular, Google, which expanded its participation in the area of education in Brazil